المنازعات المتعلقة برخصة البناء في التشريع الجزائري. - عادل, فقهي (جامعة الوادي.University eloued, 2021)
ان تنوع منازعات تراخيص أعمال التعمير والبناء يوضح اهتمام كل من القضاء الاداري والعادي في إطار بناء دولة الحق والقانون بتشجيع مراقبة قضائية موسعة وفعالة في مجال التعمير والبناء، في المقابل يلاحظ تعقيد الإجراءات من خلال الكم الهائل من الاجتهادات القضائية وتناقضها في بعض الأحيان نظرا للاختصاصات القضائية المتعددة للقاضي الإداري، القاضي المدني، القاضي الجنائي. وهو ما لا يعتبر في مصلحة المتقاضين الذين عادة ما يبحثون عن الأمن القانوني. "Abstract: The diversity of the activities of urbanism and construction permissions disputes illustrates the interest of both the administrative and ordinary courts in the light of building the State of right and the Law through promoting extensive and effective judicial monitoring in the field of urbanism and construction. In contrast, the complexity of the proceedings is noted by the vast amount of jurisprudence, which is sometimes contradicted by the multiple jurisdictions of the administrative judge, the civil judge and the criminal judge. This is not considered to be in the interest of litigants who usually seek legal security. "
ماستر قانون عقاري
Keywords: المنازعات المتعلقة برخصة البناء في التشريع الجزائري ، رخصة البناء، منازعات البناء،; disputes related to duilding permits in algerian legistation, construction license, construction desputes.